Shared Dispersal Patterns but Contrasting Levels of Gene Flow in Two Anadromous Salmonids Along a Broad Subarctic Coastal Gradient - Raphaël Bouchard; Charles Babin; Eric Normandeau; Amanda Xuereb; Félix Boulanger; Angela Coxon; Sanford Diamond; Robert Fireman; John Lameboy; Natasha Louttit; George Natawapineskum; Derek Okimaw; et al. (Molecular Ecology, 2025)
Dispersal is a highly variable trait influenced by life history and ecological factors, affecting gene flow when dispersers successfully reproduce. Anadromous salmonids, with their diverse migratory strategies and ecological traits, serve as an ideal model for studying dispersal evolution, showcasing significant inter‐ and intraspecific variation. Although environmental factors like temperature likely influence dispersal propensity, their effects remain poorly documented. This study compares dispersal patterns and population structure in lake whitefish ( Coregonus clupeaformis ) and brook charr ( Salvelinus fontinalis ) along the subarctic coastline of James Bay, covering four degrees of latitude. These species differ in life history and population size, representing contrasting ends of a continuum influencing dispersal and gene flow. We hypothesised that lake whitefish, with shorter freshwater residency and potentially reduced olfactory imprinting, would disperse more frequently than brook charr. Using low‐coverage whole‐genome sequencing, we found that lake whitefish exhibited broader‐scale population structure and greater long‐distance dispersal capacity than brook charr. Surprisingly, both species showed similar dispersal rates and population differentiation levels. However, lake whitefish had effective population sizes approximately 10 times larger than brook charr, indicating that while their dispersal is common, it results in lower effective gene flow. Moreover, dispersal rates in both species were lower in the northern study area, likely due to colder temperatures, delayed ice break and shorter growing seasons. These findings yield insights into how life history and environmental variation shape dispersal evolution in migratory species.